KONSEP TAKFĬR SAYYID QUṬB DALAM SURAH AL-MĀ’IDAH: (Analisis Maqāṣid Al-Qur’ān Perspektif Aḥmad al-Raysūnĭ) (At-Tibyan, 2023)
Takfĭr has become a highly controversial issue in recent decades. One of the most notable Islamic figures with takfĭr understanding is Sayyid Quṭb. This is completely contrary to the purpose of deriving the Qur'an which carries the mission of rahmat li al-'ālamĭn. Thematic methods and maqāṣid al-Qur'ān approaches offered by Aḥmad Al-Raysūnĭ, the author wants to reveal the main purposes of the Qur'an from the takfĭr verses in this surah al-Māidah. And managed to get the following research findings: a) The author strongly agrees with what Sayyid Quṭb said that every action must be of worship value to fulfill man's sacred promise to worship only Allah, b) Enforcing khilāfat al-islāmĭyah is a noble ideal, but if it is to be enforced with the harākat al-islāmĭyah which overrides humanity it cannot be justified because it is contrary to the maqṣad of the Qur'an to spread affection and happiness, c) People who are not punished by the law of Allah cannot be considered apostate infidels, because there are many kinds of paganism and not all of them can be considered out of religion